2011
DOI: 10.1074/jbc.m111.260141
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Prothrombinase Assembly and Activity by Phosphatidylethanolamine

Abstract: Background: PS is an allosteric regulator lipid that appears on activated platelets along with PE. Results: We show that PE 1) increases the k cat and decreases K m of thrombin formation; 2) reduces membrane surface packing to promote Va binding; and 3) binds to Va and Xa to trigger their tight association. Conclusion: This suggests a role in initiating blood coagulation. Significance: PE may also be a regulator lipid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Phosphatidylethanolamine (PE) is a class of phospholipids found in biofilms that make up 25% of all phospholipids and are important precursors, substrates and donors in multiple biological pathways (Vance & Tasseva, ; Wellner, Diep, Janfelt, & Hansen, ). Studies have shown that, in the process of blood coagulation, PE and phosphatidylserine can increase the rate of formation of thrombin and promote blood coagulation by promoting the binding with coagulation factors (Majumder, Liang, Quinn‐Allen, Kane, & Lentz, ). Compared with the NC group, the levels of phosphorylcholine, PC, PE and LysoPC in BSS group were significantly increased (Figure ), indicating that glycerophospholipid metabolism was disrupted in BSS rats and this result is consistent with the findings of Han et al ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphatidylethanolamine (PE) is a class of phospholipids found in biofilms that make up 25% of all phospholipids and are important precursors, substrates and donors in multiple biological pathways (Vance & Tasseva, ; Wellner, Diep, Janfelt, & Hansen, ). Studies have shown that, in the process of blood coagulation, PE and phosphatidylserine can increase the rate of formation of thrombin and promote blood coagulation by promoting the binding with coagulation factors (Majumder, Liang, Quinn‐Allen, Kane, & Lentz, ). Compared with the NC group, the levels of phosphorylcholine, PC, PE and LysoPC in BSS group were significantly increased (Figure ), indicating that glycerophospholipid metabolism was disrupted in BSS rats and this result is consistent with the findings of Han et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidylethanolamine (PE) is a class of phospholipids found in biofilms that make up 25% of all phospholipids and are important precursors, substrates and donors in multiple biological pathways (Vance & Tasseva, 2013;Wellner, Diep, Janfelt, & Hansen, 2013). Studies have shown that, in the process of blood coagulation, PE and phosphatidylserine can increase the rate of formation of thrombin and promote blood coagulation by promoting the binding with coagulation factors (Majumder, Liang, Quinn-Allen, Kane, & Lentz, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…125,[136][137][138] In addition to PS, the anionic PE has also been shown to bind coagulation factor Va with a high affinity (*10 nM kDa) and promote thrombin generation. 139 Despite strong circumstantial clinical and laboratory evidence, the role of brain-derived phospholipids in the development of TBIassociated coagulopathy remains unknown. Phospholipids released from injured neural cells, are also highly susceptible to oxidation.…”
Section: Phosphatidylserine and Brain Phospholipidsmentioning
confidence: 99%
“…While PS is the most significant phospholipid that regulates the structure and function of coagulation proteins such as fXa, fIXa, and fVa [ 12 14 ], other phospholipids also play crucial roles in coagulation. PE, another phospholipid abundant in activated platelet, was reported to modulate APC-mediated inactivation of fVa [ 15 ], promote the assembly and activity of the prothrombinase (fXa-fVa) complex [ 16 ], and regulate the structure and activity of fVIIa [ 17 ], (unpublished data). Again, fVIIa and activated protein C (APC) were reported to preferentially bind to nanobilayers containing PA [ 18 ].…”
Section: Introductionmentioning
confidence: 99%